2006
DOI: 10.2331/suisan.72.1046
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and migration of rabbitfish Siganus fuscescens and grey seachub Kyphosus bigibbus off Nomozaki, Kyushu, tracked by biotelemetry method

Abstract: Nomozaki, where a relatively high-density seaweed patch remained, and were tracked for more than 4 months using a biotelemetry system. During the survey, signals from the S. fuscescens were recorded with high frequency in the daytime and with low frequency at night. These was a similar trend of signals from K. bigibbus, but nove was recorded at night. The total signals per day decreased when the water temperature fell to 20°C for S. fuscescens and to 16 17°C for K. bigibbus. The movement patterns of S. fusces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…Moreover, the set-net method caught significant amounts of rabbitfish in the southeastern waters of the PHI. This is in accordance with Yamaguchi et al (2006), who indicated that the gut contents of rabbitfish were fuller at 18 -23°C than at 14 -19°C; that is, cold-water intrusion positively affected the feeding activity and movement route of the rabbitfish. Speculation on the possible effect of the cold-water event on yellowfin horse mackerel is not possible because of insufficient catch data.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, the set-net method caught significant amounts of rabbitfish in the southeastern waters of the PHI. This is in accordance with Yamaguchi et al (2006), who indicated that the gut contents of rabbitfish were fuller at 18 -23°C than at 14 -19°C; that is, cold-water intrusion positively affected the feeding activity and movement route of the rabbitfish. Speculation on the possible effect of the cold-water event on yellowfin horse mackerel is not possible because of insufficient catch data.…”
Section: Discussionsupporting
confidence: 76%
“…We expand on the findings of existing studies on the behavioural and reproductive ecology and feeding habits of K. bigibbus (Yamaguchi et al 2006(Yamaguchi et al , 2011Yamaguchi 2010) by clarifying several life history traits for this species. However, details of the early life history, population dynamics and population structure of K. bigibbus remain unclear.…”
Section: Discussionmentioning
confidence: 95%
“…The movement patterns of resident individuals demonstrate high fidelity to particular patch reefs and large home ranges, leading to large-scale landscape changes in the form of areas largely devoid of macroalgae (termed 'halos') around patch reefs (Downie et al 2013;Pillans et al 2017). On the west coast of Kyushu, Japan, K. bigibbus migrates diurnally, and its activity declines markedly when the seawater temperature decreases to ,178C (Yamaguchi et al 2006;Yamaguchi 2010). The spawning and maturation patterns of this species have been elucidated only in populations inhabiting this region.…”
Section: Introductionmentioning
confidence: 99%
“…Diel movements, in some cases associated with feeding, foraging, antipredator, and sheltering behavior, have been previously documented in marine demersal fish, including herbivorous fish [30][31][32], reef fish [33][34][35], ocean pelagic fish [14,36], and freshwater fish, including a catfish [22,23,37]. No predators of the relatively large ([0.6 m) study fish were present in this study.…”
Section: Diel Movementmentioning
confidence: 86%